2019
DOI: 10.1111/rda.13485
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor‐9 improves development, mitochondrial activity and meiotic resumption of sheep oocytes after in vitro culture of secondary follicles

Abstract: This study analysed the effect of growth differentiation factor‐9 (GDF‐9) on the in vitro culture of isolated ovine secondary follicles. The follicles were cultured in α‐MEM supplemented with BSA, insulin, glutamine, hypoxanthine, transferrin, selenium, ascorbic acid and FSH (α‐MEM+—control medium) or α‐MEM+ supplemented with 1, 10, 50 or 100 ng/ml GDF‐9. Next, the oocytes were destined to in vitro maturation (IVM). After 12 days of culture, there were no differences regarding the percentage of normal follicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…GCs as the ovarian’s primary functional units, are instrumental in follicular growth and maturation, offering nutritional support and secreting hormones imperative for follicular development ( 5 , 7 , 29 ). Notably, Loc105611671 was identified in the follicles of Qira Black sheep during estrus, implicating a regulatory effect on follicular development through GC modulation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCs as the ovarian’s primary functional units, are instrumental in follicular growth and maturation, offering nutritional support and secreting hormones imperative for follicular development ( 5 , 7 , 29 ). Notably, Loc105611671 was identified in the follicles of Qira Black sheep during estrus, implicating a regulatory effect on follicular development through GC modulation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…As they progress toward ovulation, GCs undergo morphological changes and proliferate ( 4 ). As the predominant cell type within the follicle, GCs not only regulate their own proliferation but also contribute to follicle development by synthesizing hormones (E 2 , P 4 ) ( 5 , 6 ) and growth factors ( 7 , 8 ). The process begins with the transformation of cholesterol, during which the STAR protein plays a pivotal role in translocating cholesterol to the inner mitochondrial membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research has revealed some potential mechanisms underlying this association. GDF9 was reported to enhance mitochondrial activity, meiotic resumption, and secondary follicle development in sheep [25], and GDF9 was also shown to enhance granulosa cell proliferation [26]. Further study indicated that GDF9 is required for normal folliculogenesis in many mammal species [17]; therefore, GDF9 may be a direct factor that influences litter size in ewes by affecting functions of granulosa cells and folliculogenesis.…”
Section: Reproductive Functions Of Gdf9 and Its Interactions With Nlrmentioning
confidence: 97%